Hepatobiliary Cystadenoma Revealed by a Jaundice: A Case Report - Taoufiq Harmouch; Marie-pierre Vullierme; Alain Sauvanet; Valérie Paradis; Affaf Amarti (Case Reports in Gastrointestinal Medicine)
Introduction. Hepatobiliary cystadenomas are rare benign cystic tumors and have a potential for recurrence and malignant transformation. The diagnosis may be very difficult because of absence of typical imaging feature in some cases. Case Presentation. In this paper, the authors discuss a 57-year-old woman who presented a jaundice related to hepatobiliary cystadenoma. Biological and radiological examinations have led to surgery, and the diagnosis is made after a histological examination of surgical specimens. Conclusion. This observation illustrates a hepatobiliary cystadenoma revealed by jaundice. Histology examination contributed to diagnosis. The authors discussed the mechanisms of biliary obstruction and differential diagnoses through a review of the literature.